Modified conjugated diene polymer, method for producing same, polymer composition, crosslinked product, and tire

By using modified conjugated diene polymers in rubber materials for automotive tires, combining aromatic vinyl compounds and specific element compounds, the existing materials have solved the disadvantages in wet grip performance, wear resistance and strength. The balance problem has achieved excellent performance improvement.

CN119451997APending Publication Date: 2025-02-14ENEOS MATERIALS CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380050062.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-05
Filing Date
2023-08-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing rubber materials for automotive tires have imbalances in terms of wet grip performance, wear resistance and strength, which is difficult to meet the needs of improving wet grip performance and wear resistance.

Method used

Using a modified conjugated diene polymer, the glass transition temperature relationship of the polymer is adjusted to improve the filler by introducing structural units derived from aromatic vinyl compounds during the polymerization process and using specific elemental compounds as functional groups. Dispersibility, thereby obtaining excellent wet grip performance, wear resistance and strength.

Benefits of technology

Crosslinked objects with excellent wet grip performance and wear resistance and high strength are achieved, meeting the demand for improving the performance of automobile tire materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451997A_ABST
    Figure CN119451997A_ABST
Patent Text Reader

Abstract

A modified conjugated diene-based polymer including: a structural unit derived from a conjugated diene compound; and a structural unit derived from an aromatic vinyl compound, and when Tgr (unit: K) is the glass transition temperature measured in accordance with Japan Industrial Standard K 6240: 2011 and Tgcl (unit: K) is the glass transition temperature obtained by numerical formula (1), Tgr and Tgcl satisfy the relationship of numerical formula (2). WAr is the mass fraction of the structural unit derived from the aromatic vinyl compound in the modified conjugated diene polymer, and 0 < = WAr < = 1 is satisfied. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS]

[0002] This application claims priority based on Japanese Patent Application No. 2022-125827 filed on August 5, 2022, the entire contents of which are incorporated into this specification by reference.

[0003] The present disclosure relates to a modified conjugated diene polymer, a method for producing the same, a polymer composition, a cross-linked product and a tire. Background Art

[0004] Conjugated diene polymers obtained by polymerization using conjugated diene compounds have excellent properties such as heat resistance, wear resistance, mechanical strength, and moldability, and are therefore widely used in various industrial products such as pneumatic tires, anti-vibration rubbers, and hoses.

[0005] As polymer compositions for manufacturing treads, sidewalls, etc. of pneumatic tires, it is known that fillers such as carbon black or silica are mixed with conjugated diene polymers in order to improve the durability or wear resistance of the product. In addition, in the past, in order to improve the affinity between the conjugated diene polymer and the filler, modified conjugated diene polymers modified with compounds containing silicon or nitrogen were used (for example, see Patent Documents 1 to 3).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2008 / 123164

[0009] Patent Document 2: Japanese Patent Laid-Open No. 11-349632

[0010] Patent Document 3: International Publication No. 2017 / 221943 Summary of the invention

[0011] Problems to be solved by the invention

[0012] Due to recent environmental conditions, increased awareness of resource and energy conservation, and increased consumer demand for safety, rubber for automobile tires is desired to have various properties such as wet grip performance (i.e., wet road safety), wear resistance, and strength that are improved in a well-balanced manner compared to the past.

[0013] The present disclosure has been made in view of the above problems, and a main object of the present disclosure is to provide a modified conjugated diene polymer that can provide a cross-linked product having excellent wet grip performance and abrasion resistance and high strength.

[0014] Technical means of solving problems

[0015] According to the present disclosure, the following modified conjugated diene polymer, a method for producing the same, a polymer composition, a cross-linked product, and a tire are provided.

[0016] [1] A modified conjugated diene polymer comprising: a structural unit derived from a conjugated diene compound; and a structural unit derived from an aromatic vinyl compound, wherein the glass transition temperature measured according to Japanese Industrial Standards (JIS) K 6240: 2011 is defined as Tg r (unit: K), the glass transition temperature obtained by the following formula (1) is defined as Tg cl (Unit: K), Tg r With Tg cl The relationship of the following formula (2) is satisfied.

[0017] [Number 1]

[0018]

[0019] Tg r -Tg cl ≦-6.0…(2)

[0020] (In equation (1), W Ar is the mass fraction of the structural unit derived from the aromatic vinyl compound in the modified conjugated diene polymer, satisfying 0≦W Ar ≦1. )

[0021] [2] A polymer composition comprising the modified conjugated diene polymer according to [1] above; and at least one filler selected from the group consisting of silica and carbon black.

[0022] [3] A cross-linked product obtained by cross-linking the polymer composition according to [2].

[0023] [4] A tire having a tread, a sidewall, or both formed using the polymer composition according to [2].

[0024] [5] A method for producing a modified conjugated diene polymer according to the above [1], comprising: a polymerization step of polymerizing monomers containing a conjugated diene compound and an aromatic vinyl compound in the presence of at least one polymerization initiator selected from the group consisting of an alkali metal compound and an alkaline earth metal compound, and a potassium compound (excluding the polymerization initiator), wherein in the polymerization step, polymerization is started using a portion of the total amount of the conjugated diene compound used in the polymerization as an initial charge, and the remaining conjugated diene compound is added for a predetermined time in the middle of the polymerization to continue the polymerization.

[0025] Effects of the Invention

[0026] According to the modified conjugated diene polymer of the present disclosure, a cross-linked product having excellent wet grip performance and abrasion resistance and high strength can be obtained. DETAILED DESCRIPTION

[0027] Hereinafter, matters related to the form of the present disclosure will be described in detail. In addition, the present invention is not limited to the embodiments described below, and it should be understood that it also includes various modified embodiments implemented within the scope of the present invention. In this specification, the numerical range recorded as "X to Y" represents a numerical range that includes the numerical value X as the lower limit and the numerical value Y as the upper limit. The description of "(meth)acrylic acid" is a concept that includes both "acrylic acid" and "methacrylic acid".

[0028] 《Modified conjugated diene polymers》

[0029] The modified conjugated diene polymer (hereinafter also referred to as "modified copolymer (P)") disclosed in the present invention is a polymer in which a functional group for modifying the conjugated diene polymer is introduced into one or more of the terminal part, side chain part and branch point part of the molecular chain in the conjugated diene polymer containing a structural unit derived from a conjugated diene compound and a structural unit derived from an aromatic vinyl compound. In addition, the so-called "functional group" is a group having a specific structure (specifically, a structure containing a heteroatom) in the molecule of an organic compound, and refers to an atomic group or bonding mode that imparts characteristics to the compound.

[0030] As the conjugated diene compound constituting the modified copolymer (P), for example, 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 1,3-heptadiene, 2-phenyl-1,3-butadiene, 3-methyl-1,3-pentadiene, 2-chloro-1,3-butadiene, etc. are listed. Among these, 1,3-butadiene, isoprene, or 2,3-dimethyl-1,3-butadiene is preferred. The conjugated diene compound constituting the modified copolymer (P) may be one of these, or two or more thereof.

[0031] Examples of the aromatic vinyl compound constituting the modified copolymer (P) include styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, α-methylstyrene, 2,4-dimethylstyrene, 2,4-diisopropylstyrene, 5-tert-butyl-2-methylstyrene, vinylethylbenzene, divinylbenzene, trivinylbenzene, divinylnaphthalene, tert-butoxystyrene, vinylbenzyldimethylamine, (4-vinylbenzyl)dimethylaminoethylether, N,N-dimethylaminoethylstyrene, N,N-dimethylaminomethylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2-tert-butylstyrene, 3-tert-butylstyrene, 4-tert-butylstyrene, vinylxylene, vinylnaphthalene, vinylpyridine, diphenylethylene, and diphenylethylene containing a tertiary amino group (e.g., 1-(4-N,N-dimethylaminophenyl)-1-phenylethylene). Among these, the aromatic vinyl compound is preferably styrene or α-methylstyrene. The aromatic vinyl compound constituting the modified copolymer (P) may be one kind or two or more kinds thereof.

[0032] In the case of obtaining a polymer composition prepared by blending a modified copolymer (P) and a filler (particularly silica), the modified copolymer (P) preferably contains a partial structure derived from a compound having one or more elements selected from the group consisting of nitrogen, silicon, sulfur, oxygen and phosphorus (hereinafter also referred to as "specific elements") (hereinafter also referred to as "modified compound"). The modified compound may be a compound capable of introducing a functional group having a specific element into a polymerization initiation terminal (hereinafter also referred to as "initiation terminal modifier"), or a compound capable of introducing a functional group having a specific element into a polymerization termination terminal (hereinafter also referred to as "terminal modifier"). In addition, the modified compound may also be a monomer capable of introducing a functional group having a specific element into a side chain of a molecular chain (hereinafter also referred to as "modified monomer"). In terms of a high effect of improving the dispersibility of the filler, the modified compound is preferably at least one selected from the group consisting of an initiation terminal modifier and a terminal modifier, and more preferably contains a terminal modifier.

[0033] Regarding the modified polymer (P), when the glass transition temperature measured according to JIS K 6240: 2011 is defined as Tg r (unit: K), the glass transition temperature obtained by the following formula (1) is defined as Tg cl (Unit: K), Tg r With Tg cl The relationship of the following formula (2) is satisfied.

[0034] [Number 2]

[0035]

[0036] Tg r -Tg cl ≦-6.0…(2)

[0037] (In equation (1), W Ar is the mass fraction of the structural unit derived from the aromatic vinyl compound in the modified conjugated diene polymer, satisfying 0≦W Ar ≦1. )

[0038] The modified copolymer (P) preferably has an endothermic peak in the temperature range of -100°C to 20°C in differential scanning calorimetry (DSC) according to JIS K 6240:2011. The inflection point of the DSC curve obtained by DSC analysis, that is, the peak top temperature of the differential curve is the measured value of the glass transition temperature of the modified copolymer (P). The modified copolymer (P) preferably has a glass transition temperature (measured value) of -100°C to 20°C.

[0039] In this specification, the measured value of the glass transition temperature of the modified copolymer (P) is indicated by the Celsius temperature as "measured Tg" (unit: °C), and the temperature indicated by the thermodynamic temperature is indicated by "actual glass transition temperature Tg". r ” (unit: K) or simply marked as “Tg r "(Unit: K). That is, the actual glass transition temperature Tg r (unit: K) is a value obtained by adding 273.15 to the measured Tg (unit: °C), and satisfies the following relationship.

[0040] Actual glass transition temperature Tg r (Unit: K) = measured Tg (Unit: °C) + 273.15

[0041] The measured Tg of the modified copolymer (P) is more preferably -90°C or higher, and further preferably -80°C or higher. In addition, from the viewpoint of improving the wet grip performance, the measured Tg of the modified copolymer (P) is more preferably 0°C or lower, further preferably -10°C or lower, further preferably -20°C or lower, further preferably -30°C or lower, further preferably -40°C or lower, and particularly preferably -45°C or lower. In particular, when the modified copolymer (P) has only one endothermic peak in DSC analysis and the peak temperature of the endothermic peak is in the temperature range of -100°C to 20°C, the wear resistance and strength of the crosslinked product formed using the modified copolymer (P) tend to be improved.

[0042] The above formula (1) represents an estimated formula for the glass transition temperature of a conjugated diene polymer (Journal of the Rubber Association of Japan 34 (4), 246-253, 1961). Using the above formula (1), the estimated value of the glass transition temperature of the modified copolymer (P) can be obtained. In addition, in this specification, the temperature obtained using the above formula (1) and represented by the thermodynamic temperature is denoted as "estimated glass transition temperature Tg cl ” (unit: K) or simply marked as “Tg cl ” (unit: K). That is, the estimated glass transition temperature Tg cl It is an estimated value of the glass transition temperature based on the mass fraction of the aromatic vinyl compound constituting the modified copolymer (P) and the glass transition temperature of the homopolymer of the monomer constituting the modified copolymer (P). cl (Unit: K) The value converted to Celsius temperature is also called "estimated Tg" (unit: °C).

[0043] In general, it is known that the glass transition temperature of a copolymer can be estimated based on the mass fraction of the structural units constituting the molecular chain and the glass transition temperature of a homopolymer containing the monomers constituting the copolymer. In addition, the glass transition temperature of the copolymer estimated as described above generally takes a value close to the measured value. In contrast, for the modified copolymer (P), the actual glass transition temperature Tg obtained by DSC analysis is r (Unit: K) and the estimated glass transition temperature Tg estimated by formula (1) cl (Unit: K) satisfies the relationship of the above formula (2). In other words, the measured Tg of the modified copolymer (P) is on the lower temperature side than the estimated Tg, and the absolute value of the difference between the measured Tg and the estimated Tg is as large as 6.0°C or more. According to such a modified copolymer (P), a cross-linked product having excellent wet grip performance and wear resistance and high strength can be obtained.

[0044] In addition, in the above formula (1), “W ArThe denominator of " / 380" represents the glass transition temperature of polystyrene (unit: K), "1-W Ar The denominator of " / 188" represents the glass transition temperature of polybutadiene (unit: K). In this specification, the formula (1) is determined by setting the glass transition temperature of polystyrene to 380K and the glass transition temperature of polybutadiene to 188K with reference to the sixth revised edition of "Chemical Handbook" Basic Edition, edited by the Chemical Society of Japan (Maruzen Co., Ltd.).

[0045] Here, it is presumed that the fact that the measured Tg of the modified copolymer (P) is sufficiently deviated from the low temperature side relative to the estimated Tg reflects that the modified copolymer (P) is a polymer obtained by copolymerization in a system where a conjugated diene compound and an aromatic vinyl compound coexist, and has a copolymerization part in which the arrangement order of the conjugated diene compound and the aromatic vinyl compound is irregular, and the properties of the homopolymer of the conjugated diene compound and the homopolymer of the aromatic vinyl compound are strongly expressed. In general, when copolymerization is carried out in the coexistence of a conjugated diene compound and an aromatic vinyl compound, the properties of the homopolymer of the conjugated diene compound and the homopolymer of the aromatic vinyl compound tend to be difficult to reflect because the structural units derived from the conjugated diene compound and the structural units derived from the aromatic vinyl compound are randomly arranged in the obtained copolymer. In contrast, it is believed that in the modified copolymer (P), there are multiple structures in which the structural units derived from the conjugated diene compound are continuous, and there are structures in which the structural units derived from the aromatic vinyl compound are continuous in the molecular chain, or there are regions in which the structural units derived from the conjugated diene compound are locally denser, and there are regions in which the structural units derived from the aromatic vinyl compound are locally denser in the molecular chain. Thus, it can be considered that in the modified copolymer (P), the respective properties of the homopolymer of the conjugated diene compound and the homopolymer of the aromatic vinyl compound are more strongly reflected. As a result, according to the modified copolymer (P), it is speculated that a cross-linked product with excellent wet grip performance and wear resistance and high strength can be obtained. In addition, the above-mentioned mechanism of action is only speculated and does not limit the present invention in any way.

[0046] In the modified copolymer (P), from the viewpoint of obtaining a cross-linked product having excellent wet grip performance and abrasion resistance and high strength, the actual glass transition temperature Tg r Subtract the estimated glass transition temperature Tg clThe value obtained (hereinafter also referred to as "difference ΔTg") is preferably -6.3K or less, more preferably -7.0K or less, and further preferably -7.5K or less. In addition, by controlling the amount or distribution of the structural unit derived from the aromatic vinyl compound in the molecular chain, a modified conjugated diene polymer satisfying the above formula (2) can be obtained. Specifically, the difference ΔTg can be adjusted by adjusting the amount of the conjugated diene compound added during the polymerization, the amount of the potassium compound used, the amount of the vinyl content adjuster used, and the polymerization temperature.

[0047] The ΔTg (=Tg r -Tg cl ), in this specification, the actual glass transition temperature Tg r First, the measured Tg (unit: K) was calculated based on the DSC measurement results according to JIS K 6240: 2011 as a single-digit value, and 273.15 was added to the measured Tg. cl (Unit: K) is obtained by using the above formula (1) to the second decimal place (the third decimal place is rounded off). In this specification, the actual glass transition temperature Tg obtained in this way is r Subtract the estimated glass transition temperature Tg cl The value obtained by rounding off the subtracted value to the second decimal place is taken as the difference ΔTg and compared with the judgment value (-6.0).

[0048] From the viewpoint of making the cross-linked product obtained using the modified copolymer (P) have a good balance between the low hysteresis loss characteristics and the wet grip performance and the viewpoint of making the processability of the polymer composition containing the modified copolymer (P) good, the content ratio of the structural unit derived from the aromatic vinyl compound in the modified copolymer (P) is preferably 3% by mass to 55% by mass relative to the total amount of the structural units constituting the modified copolymer (P). The content ratio of the structural unit derived from the aromatic vinyl compound is more preferably 5% by mass or more, further preferably 10% by mass or more, further preferably 15% by mass or more, and particularly preferably 20% by mass or more relative to the total amount of the structural units constituting the modified copolymer (P). In addition, the content ratio of the structural unit derived from the aromatic vinyl compound in the modified copolymer (P) is more preferably 50% by mass or less, further preferably 45% by mass or less, further preferably 40% by mass or less, and particularly preferably 35% by mass or less relative to the total amount of the structural units constituting the modified copolymer (P). In addition, the content ratio of the structural unit derived from the aromatic vinyl compound in the modified copolymer (P) is determined by 1 H-NMR ( 1H-nuclear magnetic resonance, 1 The value obtained by H-NMR) measurement.

[0049] The modified copolymer (P) is preferably 1 In the H-NMR spectrum, there is a peak in the chemical shift range of 6.00≦σ<6.89 (σ represents chemical shift (unit: ppm)). In addition, it is clarified that the peak appearing in the chemical shift range of 6.00≦σ<6.89 is a peak of a chain structure of three or more consecutive structural units derived from aromatic vinyl compounds in the molecular chain of the conjugated diene polymer (hereinafter also referred to as "specific chain"). In the modified copolymer (P), a specific chain is introduced into the molecular chain of the conjugated diene polymer by copolymerization of a conjugated diene compound and an aromatic vinyl compound. In this way, according to the modified copolymer (P) having a specific chain in the copolymerization part of the conjugated diene compound and the aromatic vinyl compound, a cross-linked product with high wear resistance and high strength can be obtained.

[0050] In the modified copolymer (P), the content ratio θst (unit: mass %) of the specific chain relative to the total amount of the structural units derived from the aromatic vinyl compound can be measured using deuterated chloroform as a solvent. 1 The H-NMR spectrum was calculated using the following formula (3).

[0051] θst=[(Σ(a) / Σ(a,b))×2.5]×100…(3)

[0052] (In formula (3), Σ(a) represents the integral value of the chemical shift range of 6.00≦σ<6.89; Σ(a,b) represents the total integral value of each chemical shift range of 6.00≦σ<6.89 and 6.89≦σ≦8.00)

[0053] In terms of improving the wear resistance and strength of the cross-linked product obtained and achieving good wet grip, the content ratio (θst) of the specific chain of the modified copolymer (P) is preferably 15% to 60% by mass. In the modified copolymer (P), the content ratio of the specific chain is more preferably 20% by mass or more, and more preferably 25% by mass or more, relative to the total amount of the structural units derived from the aromatic vinyl compound in the modified copolymer (P). In addition, the content ratio of the specific chain is more preferably 55% by mass or less, and more preferably 50% by mass or less, relative to the total amount of the structural units derived from the aromatic vinyl compound in the modified copolymer (P).

[0054] The vinyl bond content of the modified copolymer (P) is preferably 20% by mass or more. By making the vinyl bond content of the modified copolymer (P) 20% by mass or more, the wet grip performance of the cross-linked product obtained by the modified copolymer (P) can be made better. From the above viewpoint, the vinyl bond content of the modified copolymer (P) is more preferably 22% by mass or more, and further preferably 25% by mass or more. In addition, the vinyl bond content of the modified copolymer (P) is preferably 70% by mass or less. By making the vinyl bond content of the modified copolymer (P) 70% by mass or less, the reduction in the wear resistance of the cross-linked product obtained by the modified copolymer (P) can be suppressed. From the above viewpoint, the vinyl bond content of the modified copolymer (P) is more preferably 68% by mass or less, and further preferably 65% ​​by mass or less. In addition, in this specification, the "vinyl bond content" is a value indicating the content ratio of the structural units having 1,2-bonds in the modified copolymer (P) relative to all the structural units of 1,3-butadiene, and is obtained by 1 The value obtained by H-NMR measurement.

[0055] The modified copolymer (P) preferably has a polystyrene-equivalent weight average molecular weight (Mw) of 1.0×10 5 More preferably, 1.5×10 5 More preferably, 2.0×10 5 In addition, the Mw of the modified copolymer (P) is preferably 2.0×10 6 Below, more preferably 1.5×10 6 Below, more preferably 1.2×10 6 By setting the Mw of the modified copolymer (P) to the above range, a cross-linked product having high strength, low hysteresis loss characteristics and excellent wear resistance can be obtained. In addition, the Mw of the modified copolymer (P) mentioned here represents the weight average molecular weight (total weight average molecular weight) caused by the full peak of the GPC curve obtained by GPC measurement.

[0056] The modified copolymer (P) preferably has a peak top molecular weight of the minimum molecular weight peak (hereinafter also referred to as "first peak weight average molecular weight") of 5.0×10 4 More preferably, 8.0×10 4 More preferably, 1.0×10 5 In addition, the first peak weight average molecular weight of the modified copolymer (P) is preferably 2.0×10 6 Below, more preferably 1.5×10 6 Below, more preferably 1.2×10 6The first peak weight average molecular weight of the modified copolymer (P) is a polystyrene conversion value based on GPC.

[0057] The modified copolymer (P) has a molecular weight distribution (Mw / Mn) represented by the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of preferably 4.0 or less, more preferably 3.0 or less, and still more preferably 2.5 or less.

[0058] From the viewpoint of obtaining a cross-linked product having excellent processability and exhibiting low hysteresis loss characteristics or wet grip performance in a well-balanced manner, the modified copolymer (P) preferably has a Monet viscosity of 5 to 200. From this viewpoint, the Monet viscosity of the modified copolymer (P) is more preferably 10 or more, and further preferably 30 or more. Here, the Monet viscosity of the modified copolymer (P) is a value obtained according to JIS K6300-1:2013, using an L-type rotor, under the conditions of preheating for 1 minute, rotor operation time for 4 minutes, and temperature of 100°C.

[0059] <Method for producing modified copolymer (P)>

[0060] The method for producing the modified copolymer (P) is not particularly limited. As a preferred method for obtaining the modified copolymer (P), there can be cited a method comprising the following steps, namely, a step of polymerizing monomers containing a conjugated diene compound and an aromatic vinyl compound in the presence of at least one polymerization initiator selected from the group consisting of an alkali metal compound and an alkaline earth metal compound, and a potassium compound (hereinafter also referred to as a "polymerization step"). From the perspective of improving the wear resistance and strength of the cross-linked product obtained using the modified copolymer (P) while seeking to improve the wet grip performance, in the polymerization step, it is preferred to put a portion of the total amount of the conjugated diene compound used in the polymerization into the reactor as the initial charge portion to start the polymerization, and in the middle of the polymerization, the remaining conjugated diene compound is added to the reactor for a specified time, and the polymerization is continued. Specifically, it is preferred to produce the modified copolymer (P) by a method comprising the following polymerization step and modification step.

[0061] Polymerization process

[0062] In the polymerization process disclosed herein, it is preferred to obtain a polymer having an active terminal by polymerization of a monomer comprising a conjugated diene compound and an aromatic vinyl compound. As the polymerization method used, solution polymerization, gas phase polymerization, overall polymerization, etc. can be cited. Among these, solution polymerization is particularly preferred. In addition, as a polymerization form, any of batch polymerization and continuous polymerization can be used. When using solution polymerization, as an example of a specific polymerization method, a method for polymerizing a monomer comprising a conjugated diene compound and an aromatic vinyl compound in an organic solvent in the presence of a polymerization initiator and a potassium compound can be cited.

[0063] As monomers for manufacturing the modified copolymer (P), the conjugated diene compounds and aromatic vinyl compounds can be cited. In terms of high activity in anionic polymerization, it is preferred that the modified copolymer (P) is a polymer containing 1,3-butadiene and styrene in the monomer composition. During polymerization, compounds other than conjugated diene compounds and aromatic vinyl compounds (hereinafter, also referred to as "other monomers") can also be used as monomers. As other monomers, for example, acrylonitrile, methyl (meth) acrylate, ethyl (meth) acrylate, etc. can be cited. The proportion of other monomers used is preferably 10% by mass or less, more preferably 5% by mass or less, relative to the total amount of monomers used in the polymerization.

[0064] Specific examples of the polymerization initiator used in the polymerization include alkyl lithium, 1,4-dilithiobutane, phenyl lithium, distyrene lithium, naphthyl lithium, 1,3-bis(1-lithio-1,3-dimethylpentyl)benzene, 1,3-phenylenebis(3-methyl-1-phenylpentyl)dilithium, sodium naphthyl, potassium naphthyl, potassium ethoxide, di-n-butyl magnesium, di-n-hexyl magnesium, calcium stearate, etc. As alkyl lithium, for example, methyl lithium, ethyl lithium, n-propyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, etc. As the polymerization initiator, among these, alkali metal compounds are preferred, and lithium compounds are more preferred.

[0065] The polymerization reaction may also be carried out in the presence of a compound obtained by mixing at least one selected from the group consisting of alkali metal compounds and alkaline earth metal compounds with an initiator terminal modifier (hereinafter also referred to as "compound (MI)"). By polymerizing the monomer in the presence of compound (MI), a functional group derived from the initiator terminal modifier can be introduced into the polymerization initiation terminal of the conjugated diene polymer.

[0066] As the initiator terminal modifying agent, a nitrogen-containing compound such as a secondary amine compound can be preferably used. Specific examples of nitrogen-containing compounds include chain or cyclic secondary amine compounds such as dimethylamine, diethylamine, dipropylamine, dibutylamine, dodecamethyleneimine, N,N'-dimethyl-N'-trimethylsilyl-1,6-diaminohexane, piperidine, pyrrolidine, hexamethyleneimine, heptamethyleneimine, dicyclohexylamine, N-methylbenzylamine, di-(2-ethylhexyl)amine, diallylamine, morpholine, N-(trimethylsilyl)piperazine, N-(tert-butyldimethylsilyl)piperazine, 1,3-bis-trimethylsilyl-1,3,5-triazacyclohexane, N-trimethylsilylpiperazine, 1,3,3-trimethyl-6-azabicyclo[3.2.1]octane, and 1-propyl-3-azabicyclo[3.2.2]nonane.

[0067] Furthermore, when the polymerization is carried out in the presence of the compound (MI), at least one selected from the group consisting of alkali metal compounds and alkaline earth metal compounds may be pre-mixed with an initiator terminal modifier, and the mixture may be added to the polymerization system for polymerization. Alternatively, at least one selected from the group consisting of alkali metal compounds and alkaline earth metal compounds and an initiator terminal modifier may be added separately or simultaneously to the polymerization system, and the two may be mixed in the polymerization system for polymerization. Any of these cases is also included in the embodiment of "polymerizing the monomer in the presence of a compound obtained by mixing at least one of an alkali metal compound or an alkaline earth metal compound with an initiator terminal modifier".

[0068] The amount of the polymerization initiator used (the total amount when two or more kinds are used) is preferably 0.01 to 20 mmol, more preferably 0.05 to 15 mmol, based on 100 g of the monomer used for the synthesis of the modified copolymer (P).

[0069] Examples of potassium compounds used in the polymerization process of the present disclosure include potassium salts of organic carboxylic acids, potassium salts of organic sulfonic acids, potassium salts of organic phosphorous acids, potassium alkoxides, potassium phenolates, etc. The conjugated diene compound and the aromatic vinyl compound are polymerized in the presence of a potassium compound to control the structure of the molecular chain (specifically, the position or content ratio of a specific chain in the conjugated diene polymer is adjusted), thereby obtaining the actual glass transition temperature Tg by a simple operation. r and estimated glass transition temperature Tg cl A modified conjugated diene polymer that satisfies the relationship of the above formula (2).

[0070] Specific examples of potassium compounds include potassium alkoxides and potassium phenoxides, such as potassium isopropoxide, potassium tert-butoxide, potassium 2-methylpropoxide, potassium 1,1-dimethylpropoxide, potassium n-heptanol, potassium cyclohexanol, potassium benzyloxide, potassium 2-ethyl-1-hexanol, potassium 2-octanol, potassium 2-heptanol, potassium phenoxide, potassium 2,6-di-tert-butyl-p-methylphenolate, potassium 2,6-di-tert-butyl-p-methylphenolate, potassium octylphenolate, potassium nonylphenolate, potassium dodecylphenolate, etc. In addition, in the polymerization step of the present disclosure, as potassium alkoxide or potassium phenoxide, a complex of the exemplified potassium alkoxide or potassium phenoxide and an alcohol or amine can be used. As the alcohol or amine, a linear or cyclic aliphatic alcohol having 1 to 12 carbon atoms, a thiol, a primary amine, or a secondary amine can be mentioned.

[0071] Examples of the potassium salt of an organic carboxylic acid include potassium isovalerate, potassium octanoate, potassium laurate, potassium palmitate, potassium stearate, potassium oleate, potassium linolenate, potassium benzoate, potassium phthalate, potassium 2-ethylhexanoate, etc. In addition, as the potassium salt of an organic carboxylic acid, a complex of the potassium salt of the organic carboxylic acid exemplified above and an alcohol or amine can be used. Examples of the alcohol or amine include a linear or cyclic aliphatic alcohol having 1 to 12 carbon atoms, a thiol, a primary amine, or a secondary amine.

[0072] Examples of the potassium salt of an organic sulfonic acid include potassium dodecylbenzenesulfonate, potassium tetradecylbenzenesulfonate, potassium hexadecylbenzenesulfonate, potassium octadecylbenzenesulfonate, and the like. In addition, as the potassium salt of an organic sulfonic acid, a complex of the potassium salt of the organic sulfonic acid exemplified above with an alcohol or an amine can be used. Examples of the alcohol or amine include a linear or cyclic aliphatic alcohol having 1 to 12 carbon atoms, a thiol, a primary amine, or a secondary amine.

[0073] Examples of the potassium salt of organic phosphorous acid include potassium diethyl phosphite, potassium diisopropyl phosphite, potassium diphenyl phosphite, potassium dibutyl phosphite, potassium dilauryl phosphite, and the like.

[0074] The potassium compound used for producing the modified copolymer (P) is preferably at least one selected from the group consisting of potassium salts of organic carboxylic acids, potassium salts of organic sulfonic acids, potassium salts of organic phosphorous acids, potassium alkoxides and potassium phenoxides, and more preferably potassium salts of organic sulfonic acids. In addition, as the potassium compound, one kind may be used alone, or two or more kinds may be used in combination.

[0075] During the polymerization reaction, the use ratio of the potassium compound is preferably set to an amount of 0.005 mol to 0.5 mol relative to 1 mol of metal atoms participating in the polymerization reaction possessed by the polymerization initiator. By setting the use ratio of the potassium compound to more than 0.005 mol, the effect brought about by the addition of the potassium compound (especially the ability to adjust the proportion of the content of a specific chain in the polymer) can be fully obtained. In addition, by setting the use ratio of the potassium compound to less than 0.5 mol, the reduction of the polymerization activity can be suppressed, and the productivity can be fully ensured, or when a modification reaction of introducing a functional group into the polymer terminal is carried out, the reduction of the modification efficiency can be suppressed. From this point of view, the use ratio of the potassium compound is more preferably set to an amount of less than 0.3 mol relative to 1 mol of metal atoms participating in the polymerization reaction possessed by the polymerization initiator, and is further preferably set to an amount of less than 0.1 mol.

[0076] For the purpose of adjusting the vinyl bond content representing the content of vinyl bonds in the polymer, the polymerization reaction can be carried out in the presence of a vinyl content adjuster (also referred to as a "randomizer"). As the vinyl content adjuster, ether compounds and tertiary amine compounds can be cited. As specific examples of the vinyl content adjuster, dimethoxybenzene, tetrahydrofuran, dimethoxyethane, diethylene glycol dibutyl ether, diethylene glycol dimethyl ether, 2,2-bis(2-tetrahydrofuranyl)propane, 2-(2-ethoxyethoxy)-2-methylpropane, triethylamine, pyridine, N-methylmorpholine, tetramethylethylenediamine, etc. As the vinyl content adjuster, one can be used alone or two or more can be used in combination.

[0077] As the organic solvent used in the polymerization, as long as it is an inert solvent in the reaction. As an organic solvent, for example, chain or cyclic aliphatic hydrocarbons, aromatic hydrocarbons, etc. can be listed. Among these, preferably a hydrocarbon with a carbon number of 3 to 8, as its specific example, for example, can be listed: propane, n-butane, isobutane, n-pentane, isopentane, n-hexane, cyclohexane, propylene, 1-butene, isobutylene, trans-2-butene, cis-2-butene, 1-hexene, 2-hexene, benzene, toluene, xylene, ethylbenzene, heptane, cyclopentane, methylcyclopentane, methylcyclohexane, 1-pentene, 2-pentene, cyclohexene, etc. In addition, as an organic solvent, one can be used alone or in combination of two or more.

[0078] In the case of solution polymerization, from the viewpoint of maintaining a balance between productivity and ease of polymerization control, the monomer concentration in the reaction medium is preferably 5% by mass to 50% by mass, more preferably 10% by mass to 30% by mass. The polymerization reaction temperature is preferably -20°C to 150°C, more preferably 0°C to 120°C. In addition, the polymerization reaction is preferably carried out under a pressure sufficient to substantially keep the monomer in a liquid phase.

[0079] In the polymerization process for obtaining the modified copolymer (P), it is preferred to load a portion of the total amount of the conjugated diene compound used in the polymerization and the aromatic vinyl compound into the reactor to start the polymerization. For these monomers, they can be added to the reactor before the polymerization initiator, or the polymerization initiator can be added to the reactor first, and then the monomers can be added to the reactor. In addition, there is no particular limitation on the period for adding the potassium compound and the vinyl content adjuster, and they can be added to the reactor together with the monomers, or before or after the monomers. For the aromatic vinyl compound, it can be added to the reactor at once or in batches. From the viewpoint of operating efficiency and the viewpoint of maintaining a balance between wet grip performance and wear resistance, in the polymerization process disclosed in the present invention, it is preferred to load all the aromatic vinyl compounds used in the polymerization into the reactor to start the polymerization.

[0080] Of the total amount of the conjugated diene compound used in the polymerization, it is preferred that the remaining conjugated diene compound not used for the initial charge is added to the reactor for a predetermined time during the polymerization. The ratio of the initial charge amount Q1 of the conjugated diene compound used in the polymerization to the amount Q2 added during the polymerization is not particularly limited. From the viewpoint of improving the wear resistance and strength of the cross-linked product obtained by using the modified copolymer (P) and seeking to improve the wet grip performance, the ratio (mass ratio) of the initial charge amount Q1 to the amount Q2 added during the polymerization is preferably set to Q1:Q2=1:0.5-7, and more preferably set to Q1:Q2=1:0.7-5.

[0081] The period of adding the remaining conjugated diene compound in the middle of the polymerization is not particularly limited. The remaining conjugated diene compound can be added, for example, after confirming that the polymerization conversion rate of the monomers in the initial charge reaches 5% to 50%, or after confirming that it reaches 10% to 35%. In addition, it is preferred to spend sufficient time to add the remaining conjugated diene compound in the middle of the polymerization. Specifically, it is preferred to spend 5 minutes to 60 minutes to add the conjugated diene compound, and more preferably to spend 10 minutes to 45 minutes to add the conjugated diene compound. When the conjugated diene compound is added to the reactor in the middle of the polymerization, as long as it takes a specified time to add, the conjugated diene compound can be added continuously or in multiple stages.

[0082] Modification process

[0083] The modified copolymer (P) is preferably produced by a method including a step (also referred to as a modification step) of reacting a polymer having an active terminal obtained by the polymerization step with a compound having one or more elements selected from the group consisting of nitrogen, silicon, sulfur, oxygen and phosphorus (i.e., a terminal modifier). By reacting the polymer having an active terminal with the terminal modifier, a molecular chain containing monomer units derived from a conjugated diene compound and an aromatic vinyl compound is bonded to the terminal modifier, thereby obtaining a modified conjugated diene polymer into which a functional group having one or more elements selected from the group consisting of nitrogen, silicon, sulfur, oxygen and phosphorus is introduced. The polymer used for reacting with the terminal modifier may be an unmodified conjugated diene polymer, a modified conjugated diene polymer having a partial structure derived from the terminal modifier at the terminal portion, or a modified conjugated diene polymer containing a structural unit derived from a modified monomer.

[0084] The terminal modifier may be a compound having one functional group that can react with the active terminal possessed by the polymer obtained by the polymerization process, or a compound (coupling agent) having multiple functional groups that can react with the active terminal. The terminal modifier is preferably a compound having one or more elements selected from the group consisting of nitrogen, silicon, sulfur, oxygen and phosphorus, and more preferably a compound having at least one selected from the group consisting of a nitrogen-containing group, a hydrocarbyloxysilyl group, an epoxy group and a polysiloxane structure. In addition, a "hydrocarbyloxysilyl group" is a group in which at least one hydrocarbyloxy group is bonded to a silicon atom, and refers to a group represented by the following formula (5). "Epoxy group" includes "oxetanyl" and "oxacyclopropyl".

[0085] [Chemistry 1]

[0086]

[0087] (In formula (5), R 20 and R 21 are independently hydrocarbon groups; i is an integer from 1 to 3; when i is 1, the multiple R 21 The same or different; when i is 2 or 3, the multiple R 20 The same or different from each other; "*" indicates a bonding bond. )

[0088] Specific examples of terminal modifiers include compounds having an epoxy group, such as those described in Japanese Patent Laid-Open No. 2002-284930, International Publication No. 2008 / 123215, and Japanese Patent Laid-Open No. 2009-227858. In addition, compounds having an epoxy group and a polysiloxane structure include compounds described in Japanese Patent Laid-Open No. 2009-084413.

[0089] As the terminal modifier, a compound having one or more nitrogen-containing groups and one or more hydrocarbyloxysilyl groups in one molecule (hereinafter also referred to as "modifier (M)") can be particularly preferably used. By using the modifier (M) as the terminal modifier, the low hysteresis loss characteristics when used as a cross-linked product can be improved, which is preferred in this regard.

[0090] Specifically, the modifier (M) is preferably at least one selected from the group consisting of a compound represented by the following formula (6), a compound represented by the following formula (7), a compound represented by the following formula (8), and a compound represented by the following formula (9).

[0091] [Chemistry 2]

[0092]

[0093] (In formula (6), A 2 The invention is a material having at least one element selected from the group consisting of nitrogen, silicon, sulfur, oxygen and phosphorus, having no active hydrogen, and having a relative strength to R 17 A monovalent functional group bonded to nitrogen, silicon, sulfur, oxygen or phosphorus; R 15 and R 16 is a hydrocarbon group, R 17 is an alkylene group, r is an integer from 0 to 2; when r is 0 or 1, the multiple R 16 The same or different, when r is 2, the multiple R 15 Same or different.)

[0094] [Chemistry 3]

[0095]

[0096] (In formula (7), A 3 The invention is a material having at least one element selected from the group consisting of nitrogen, phosphorus, oxygen, sulfur and silicon, having no active hydrogen, and having a relative strength to R 22 A monovalent functional group bonded with nitrogen, phosphorus, oxygen, sulfur or silicon, or a hydrocarbon group having 1 to 20 carbon atoms; R 22 is a single bond or an alkylene group, R 23 and R 24 are independently a hydrocarbon group, R 25 is an alkylene group, t is 0 or 1; wherein, when t is 0, the multiple R 24 Same or different.)

[0097] [Chemistry 4]

[0098]

[0099] (In formula (8), R 31is an alkanediyl group having 1 to 20 carbon atoms, R 32 and R 33 are each independently a hydrocarbon group having 1 to 20 carbon atoms, 1 For the base "*-C(R 35 )=N-" or the group "*-N=C(R 35 )-”(where R 35 A hydrogen atom or a hydrocarbon group, "*" indicates a bond to R 34 Bond of 34 is an m-valent hydrocarbon group having 1 to 20 carbon atoms, or an m-valent group having 1 to 20 carbon atoms having at least one element selected from the group consisting of nitrogen, oxygen and sulfur and having no active hydrogen; n is an integer of 1 to 3, m is an integer of 2 to 10; for R 31 ~R 33 and A 1 When there are multiple identical symbols in the formula, the groups represented by the symbols are identical or different; multiple n in the formula are identical or different.)

[0100] [Chemistry 5]

[0101]

[0102] (In formula (9), R 42 , R 43 and R 45 are each independently an alkanediyl group having 1 to 12 carbon atoms, R 40 , R 41 , R 48 and R 49 are independently a hydrocarbon group having 1 to 20 carbon atoms; 4 is a nitrogen-containing heterocyclic group or a group represented by the following formula (a4);

[0103] [Chemistry 6]

[0104]

[0105] (In formula (a4), R 46 and R 47 Each independently represents a hydrocarbon group having 1 to 20 carbon atoms; a represents an integer of 1 to 3; for each symbol, when there are multiple identical symbols in the formula, the groups represented by the symbols are identical or different; "*" represents a bonding bond.

[0106] c and d are independently integers of 1 to 3, and b is an integer of 1 to 10; for each symbol, when there are multiple identical symbols in the formula, the groups represented by the symbols are identical or different. )

[0107] In the above formula (6) and formula (7), R 15 , R16 , R 23 and R 24 The hydrocarbon group represented is preferably a linear or branched alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms. 17 and R 22 Preferably, it is a linear or branched alkanediyl group having 1 to 20 carbon atoms, a cycloalkylene group having 3 to 20 carbon atoms, or an arylene group having 6 to 20 carbon atoms. 25 A linear or branched alkanediyl group having 1 to 20 carbon atoms is preferred.

[0108] A 2 It is a nitrogen-containing group, which can be a chain structure or a ring structure. 2 The nitrogen present may not be bonded to active hydrogen and may be protected by a protecting group (e.g., a trisubstituted hydrocarbylsilyl group). 2 It may be a group that can be converted into an onium ion by an onium salt generating agent.

[0109] As A 2 Specific examples include: a nitrogen-containing group formed by replacing two hydrogen atoms of a primary amino group with two protecting groups, a nitrogen-containing group formed by replacing one hydrogen atom of a secondary amino group with one protecting group, a tertiary amino group, an imino group, a pyridyl group, etc. Among these, A 2 Preferably, it has at least one selected from the group consisting of a tertiary amino group, a group in which one hydrogen atom of a secondary amino group is replaced by one protecting group, a group in which two hydrogen atoms of a primary amino group are replaced by two protecting groups, and an imino group. 2 A functional group converted into a functional group inert to the polymerization active terminal. A nitrogen-containing group formed by replacing one hydrogen atom of a secondary amino group with a protective group and a tertiary amino group may be chain-shaped or cyclic.

[0110] A 3 At least one element selected from the group consisting of nitrogen, phosphorus, oxygen, sulfur and silicon may not bond with active hydrogen and may be protected by a protecting group (such as a trisubstituted hydrocarbylsilyl group, etc.). 3 It may be a group that can be converted into an onium ion by an onium salt generating agent.

[0111] As A 3Specific examples include: a nitrogen-containing group in which two hydrogen atoms of a primary amino group are replaced by two protecting groups, a nitrogen-containing group in which one hydrogen atom of a secondary amino group is replaced by one protecting group, a tertiary amino group, an imino group, a pyridyl group, a phosphorus-containing group in which two hydrogen atoms of a primary phosphine group are replaced by two protecting groups, a phosphorus-containing group in which one hydrogen atom of a secondary phosphine group is replaced by one protecting group, a tertiary phosphine group, a group in which a hydrogen atom of a hydroxyl group is protected by a protecting group, a sulfur-containing group in which a hydrogen atom of a thiol group is replaced by a protecting group, and a hydrocarbyloxysilyl group. Among these, A 3 It is preferably a group having silicon or nitrogen, and more preferably a hydrocarbyloxysilyl group, a nitrogen-containing group having a protective group, or a tertiary amino group.

[0112] In the formula (8), R 31 Examples of the alkylene group include an alkanediyl group having 1 to 12 carbon atoms, a cycloalkylene group having 3 to 12 carbon atoms, and an arylene group having 6 to 12 carbon atoms. 32 and R 33 Examples of the hydrocarbon group include an alkyl group having 1 to 20 carbon atoms, an allyl group, a cycloalkyl group having 3 to 20 carbon atoms, and an aryl group having 6 to 20 carbon atoms.

[0113] R 34 The m-valent hydrocarbon group represented by is a group obtained by removing m hydrogen atoms from a hydrocarbon. 34 The m-valent hydrocarbon group represented is preferably a group formed by removing m hydrogen atoms from the ring part of an aromatic hydrocarbon (m-valent aromatic ring group). Specific examples of the aromatic hydrocarbon include monocyclic or condensed rings such as a benzene ring, a naphthalene ring, and an anthracene ring, and structures formed by two or more of these rings being bonded by a single bond.

[0114] In R 34 In the case of an m-valent group having 1 to 20 carbon atoms and having at least one element selected from the group consisting of nitrogen, oxygen and sulfur and having no active hydrogen, specific examples thereof include an m-valent heterocyclic group, an m-valent group having a tertiary amine structure, etc. The heterocyclic group is preferably a conjugated system, and examples thereof include a monocyclic or condensed ring such as pyridine, pyrimidine, pyrazine, quinoline, naphthyridine, furan, thiophene, or a group formed by removing m hydrogen atoms from a ring portion of a structure formed by connecting a plurality of rings therein.

[0115] From the viewpoint of improving the processability of the polymer composition containing the modified copolymer (P), m is preferably 2 to 6. From the viewpoint of achieving a higher effect of improving the dispersibility of silica, n is preferably 2 or 3, more preferably 3.

[0116] In the formula (9) and formula (a4), R 45 , R 42 and R 43 The alkanediyl group is preferably straight-chain. 40 , R41 , R 46 ~R 49 Examples of the hydrocarbon group include an alkyl group having 1 to 20 carbon atoms, an allyl group, a cycloalkyl group having 3 to 20 carbon atoms, and an aryl group having 6 to 20 carbon atoms.

[0117] In A 4 In the case of a nitrogen-containing heterocyclic group, the nitrogen-containing heterocyclic group is preferably a group derived from a conjugated heterocyclic system. Examples of the nitrogen-containing heterocyclic group include a group obtained by removing a hydrogen atom from a nitrogen-containing heterocyclic ring such as pyrrole, imidazole, pyridine, pyrimidine, pyrazine, quinoline, naphthyridine or benzimidazole.

[0118] From the viewpoint of achieving a higher effect of improving the dispersibility of silica, a, c and d are preferably 2 or 3, more preferably 3. b is preferably 1-5, more preferably 1-3.

[0119] Specific examples of the terminal modifier include compounds represented by formula (6), such as N,N-bis(trimethylsilyl)aminopropyltrimethoxysilane, N,N-bis(trimethylsilyl)aminopropylmethyldiethoxysilane, 1-phenyl-N-(3-(triethoxysilyl)propyl)methanimine, N,N',N'-tris(trimethylsilyl)-N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 3-(4-trimethylsilyl-1-piperazinyl)propylmethyldimethoxysilane, 3-(trimethylsilylmercapto)propyltrimethoxysilane, and 3-(diphenylphosphino)propylmethyldiethoxysilane.

[0120] Examples of the compound represented by the formula (7) include 1-trimethylsilyl-2,2-dimethoxy-1-aza-2-silacyclopentane, 1-triethylsilyl-2,2-diethoxy-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1,2-azasilacyclopentane, 2,2-dimethoxy-1-phenyl-1,2-azasilacyclopentane, and 2-(2,2-dimethoxy-1,2-azasilacyclopentane-1-yl)-N,N-diethylethane-1-amine.

[0121] Examples of the compound represented by the formula (8) include compounds represented by the following formulae (m-1-1) to (m-1-8),

[0122] [Chemistry 7]

[0123]

[0124] and compounds wherein the alkyl group and the alkanediyl group in the above compounds are substituted with an alkyl group having 1 to 6 carbon atoms or an alkanediyl group having 1 to 6 carbon atoms, respectively.

[0125] Examples of the compound represented by the formula (9) include tris(2-triethoxysilylethyl)amine, tris(3-triethoxysilylpropyl)amine, tris(5-triethoxysilylpentyl)amine, N,N,N',N'-tetrakis(2-triethoxysilylethyl)-1,2-diaminoethane, N,N,N',N'-tetrakis(3-triethoxysilylpropyl)-1,3-diaminopropane, N-(3-(1H-imidazol-1-yl)propyl)-3-(trimethoxysilyl)-N-(3-(trimethoxysilyl)propyl)propane-1-amine, and compounds in which the alkyl group and the alkanediyl group in these compounds are substituted with an alkyl group having 1 to 6 carbon atoms or an alkanediyl group having 1 to 6 carbon atoms, respectively.

[0126] As the terminal modifier that can be used in the synthesis of the modified copolymer (P), in addition to the above, there can be mentioned tetrachlorosilane (silicon tetrachloride), tetramethoxysilane, bis(trichlorosilyl)ethane, etc. As the terminal modifier, one of the above may be used alone, or two or more may be used in combination.

[0127] The reaction of the polymer with active terminal and the terminal modifier is preferably carried out in the form of solution reaction. From the viewpoint of making the modification reaction fully proceed, the use ratio of the terminal modifier (the total amount when using two or more) is preferably set to 0.01 mol or more, and more preferably set to 0.05 mol or more relative to 1 mol of the metal atoms participating in the polymerization possessed by the polymerization initiator. In addition, the use ratio of the terminal modifier is preferably set to less than 2.0 mol, more preferably set to less than 1.0 mol, and further preferably set to less than 0.7 mol, and further preferably set to less than 0.5 mol relative to 1 mol of the metal atoms participating in the polymerization possessed by the polymerization initiator.

[0128] The temperature of the modification reaction is usually the same as that of the polymerization reaction, preferably set to -20°C to 150°C, more preferably set to 0°C to 120°C. If the reaction temperature is low, the viscosity of the modified polymer tends to increase, and if the reaction temperature is high, the polymerization active end is easily deactivated. The reaction time is preferably 1 minute to 5 hours, more preferably 2 minutes to 1 hour. In order to separate the modified copolymer (P) contained in the reaction solution, for example, it can be carried out by a known desolventizing method such as steam stripping and a drying operation such as a heat treatment.

[0129] 《Polymer composition》

[0130] The polymer composition of the present disclosure contains: the modified copolymer (P); and at least one filler selected from the group consisting of silica and carbon black. In addition, the polymer composition of the present disclosure may further contain various components other than the modified copolymer (P), silica and carbon black.

[0131] [B]Silicon dioxide

[0132] The polymer composition disclosed herein may contain [B] silica. The amount of [B] silica blended is preferably in the range of 20 to 200 parts by mass, and more preferably in the range of 30 to 150 parts by mass, relative to 100 parts by mass of the rubber component containing the modified copolymer (P). If the amount of [B] silica blended is 20 parts by mass or more relative to 100 parts by mass of the rubber component, the low hysteresis loss characteristics, fracture characteristics and wear resistance of the cross-linked product obtained by the polymer composition can be sufficiently improved. In addition, if it is 200 parts by mass or less, the processability of the polymer composition can be sufficiently improved.

[0133] In addition, in this specification, the "rubber component" contained in the polymer composition refers to a polymer that can obtain a cured product exhibiting rubber elasticity by curing, etc. The cured product exhibits the following properties: it undergoes a large deformation with a small force at room temperature (for example, it deforms to more than twice when stretched at room temperature), and quickly returns to substantially the original shape when the force is removed.

[0134] [B] silica is not particularly limited, and examples thereof include wet silica (hydrous silicic acid), dry silica (anhydrous silicic acid), calcium silicate, aluminum silicate, etc. Among these, wet silica is preferred. [B] silica may be used alone or in combination of two or more. In addition, the Brunauer-Emmett-Teller (BET) specific surface area of ​​[B] silica (the value measured according to ISO 5794 / 1) is preferably 10 m 2 / g~350m 2 / g, and more preferably 20 m 2 / g~300m 2 / g, particularly preferably 30 m 2 / g~250m 2 / g range. Silica with a BET specific surface area within the above range has the following advantages: it can take into account both rubber reinforcement and dispersibility in the modified copolymer (P). As such silica, the trade name "Nipsil AQ" (BET specific surface area = 205 m 2 / g), Nipsil KQ, and Ultrasil VN3 manufactured by Degussa (BET specific surface area = 175 m 2 / g) and other commercially available products.

[0135] The silica contained in the polymer composition may be used in combination of two or more silicas having different specific surface areas. Specifically, CTAB (cetyltrimethylammonium bromide) having a specific surface area of ​​180 m 2 / g or more, BET specific surface area of ​​185m 2 The specific surface area of ​​the first silica with an aggregate size of 45 nm or more and CTAB is 95 m 2 / g or less, BET specific surface area of ​​100m 2 The CTAB specific surface area of ​​silica is measured in accordance with American Society for Testing Materials (ASTM) D3765-92.

[0136] One form of the polymer composition contains CTAB with a specific surface area of ​​180 m 2 / g or more, BET specific surface area of ​​185m 2 The specific surface area of ​​the first silica and CTAB is 95m 2 / g or less, BET specific surface area of ​​100m 2 By using the first silica and the second silica together, the first silica having a small average primary particle size but a relatively large aggregate size can be well dispersed in the rubber component, thereby improving the dispersibility of the silica and obtaining excellent rubber breaking strength, wear resistance, low hysteresis loss characteristics and processability.

[0137] The CTAB specific surface area of ​​the first silica is preferably 190 m 2 / g or more, more preferably 195m 2 / g or more, more preferably 197m 2 / g or more. If the specific surface area of ​​CTAB is 190m 2 / g or more, there is a tendency to sufficiently improve the rubber breaking strength and abrasion resistance of the cross-linked product obtained by the polymer composition. The CTAB specific surface area is preferably 350m 2 / g or less, more preferably 300m 2 / g or less, and more preferably 250m 2 / g or less. If the specific surface area of ​​CTAB is 350m 2 / g or less, silica is less likely to aggregate, and there is a tendency that physical properties can be improved.

[0138] The BET specific surface area of ​​the first silica is preferably 190 m 2 / g or more, more preferably 195m 2 / g or more, more preferably 210m 2 / g or more. If the BET specific surface area is 190m 2 / g or more, there is a tendency to sufficiently improve the rubber breaking strength and abrasion resistance of the cross-linked product obtained by the polymer composition. The BET specific surface area is preferably 350 m 2 / g or less, more preferably 300m 2 / g or less, and more preferably 260m 2 / g or less. If the BET specific surface area is 350m 2 / g or less, silica is less likely to aggregate, and there is a tendency that physical properties can be improved. The BET specific surface area of ​​silica is measured in accordance with ASTM D3037-81.

[0139] The aggregation size of the first silica is preferably more than 45nm, more preferably more than 50nm, and more preferably more than 55nm, and more preferably more than 60nm. In addition, the aggregation size is preferably less than 100nm, more preferably less than 80nm, and more preferably less than 70nm, and more preferably less than 67nm. By having such an aggregation size, it is possible to impart excellent low hysteresis loss characteristics and wear resistance while having good dispersibility (processability). In addition, the aggregation size of silica can be determined by the method described in Japanese Patent Gazette No. 2011-140613.

[0140] The average primary particle size of the first silica is preferably less than 25nm, more preferably less than 22nm, and further preferably less than 17nm, and particularly preferably less than 14nm. The lower limit of the average primary particle size is not particularly limited, preferably more than 3nm, more preferably more than 5nm, and further preferably more than 7nm. Although having such a small average primary particle size, the dispersibility (processability) of silica can be further improved by a structure such as carbon black having the aggregation size, and the low hysteresis loss characteristics and wear resistance can be further improved. In addition, the average primary particle size of silica can be observed by a transmission electron microscope or a scanning electron microscope. The particle size of the primary particles of more than 400 silica observed in the field of view is measured, and the average is obtained.

[0141] The CTAB specific surface area of ​​the second silica is preferably 10 m 2 / g or more, more preferably 20m 2 / g or more, more preferably 30m 2 / g or more. If the specific surface area of ​​CTAB is less than 10m 2 / g, the reinforcement property is reduced, and it may become difficult to ensure the mechanical strength or wear resistance required for the polymer composition for tire manufacturing. The CTAB specific surface area is preferably 80m 2 / g or less, more preferably 60m 2 / g or less, and more preferably 50m 2 / g or less. If the CTAB specific surface area exceeds 95m 2 / g, the dispersibility of silica deteriorates, and there is a possibility that it becomes difficult to improve the rubber breaking strength and abrasion resistance.

[0142] The BET specific surface area of ​​the second silica is preferably 10 m 2 / g or more, more preferably 20m 2 / g or more, more preferably 30m 2 / g or more. If the BET specific surface area is 10m 2 / g or more, it has sufficient reinforcement and is easy to ensure the mechanical strength or wear resistance required for the polymer composition used to obtain tire rubber. The BET specific surface area is preferably 85m 2 / g or less, more preferably 60m 2 / g or less, and more preferably 50m 2 / g or less. If the BET specific surface area is 85m 2 / g or less, the silica is sufficiently dispersed, and there is a tendency to easily improve the rubber breaking strength and abrasion resistance.

[0143] The average primary particle size of the second silica is preferably 20 nm or more, more preferably 25 nm or more, further preferably 30 nm or more, particularly preferably 35 nm or more, and most preferably 55 nm or more. In addition, the average primary particle size is preferably 500 nm or less, more preferably 200 nm or less, further preferably 100 nm or less, and particularly preferably 70 nm or less. By having such an average primary particle size, the rubber breaking strength and abrasion resistance can be improved.

[0144] [C] Carbon black

[0145] From the viewpoint of the destructive characteristics and wear resistance of the polymer composition, the polymer composition disclosed in the present invention preferably contains [C] carbon black. As carbon black, there is no particular limitation, for example, general purpose furnace black (GPF), fast extruding furnace black (FEF), high abrasion furnace black (HAF), intermediate super abrasion furnace black (ISAF), super abrasion furnace black (SAF) grade carbon black. The nitrogen adsorption specific surface area (N2SA) of carbon black is not particularly limited, but for the reason of the superior effect of the present invention, it is preferably 50 m 2 / g~200m 2 / g, more preferably 70m 2 / g~150m 2 / g. Nitrogen adsorption specific surface area (N2SA) is a value obtained by measuring the amount of nitrogen adsorption on the surface of carbon black in accordance with JIS K6217-2:2001 "Part 2: Method for determining specific surface area - Nitrogen adsorption method - Single point method". These carbon blacks may be used alone or in combination of two or more. In addition, the amount of carbon black blended is preferably in the range of 1 to 150 parts by mass, and more preferably in the range of 5 to 120 parts by mass, relative to 100 parts by mass of the rubber component containing the modified copolymer (P).

[0146] Other fillers

[0147] In addition to the above-mentioned [B] silica and [C] carbon black, the polymer composition of the present disclosure may also contain other fillers as inorganic fillers. Examples of the above-mentioned other fillers include aluminum oxide (Al2O3) such as γ-alumina and α-alumina, aluminum oxide monohydrate (Al2O3·H2O) such as boehmite and diaspore, aluminum hydroxide [Al(OH)3] such as gibbsite and bayerite, aluminum carbonate [Al2(CO3)3], magnesium hydroxide [Mg(OH)2], magnesium oxide (MgO), magnesium carbonate (MgCO3), talc (3MgO·4SiO2·H2O), attapulgite (5MgO·8SiO2·9H2O), titanium dioxide (TiO2), titanium black (TiO 2n-1), calcium oxide (CaO), calcium hydroxide [Ca(OH)2], magnesium alumina (MgO·Al2O3), clay (Al2O3·2SiO2), kaolinite (Al2O3·2SiO2·2H2O), pyrophyllite (Al2O3·4SiO2·H2O), bentonite (Al2O3·4SiO2·2H2O), aluminum silicate (Al2SiO5·Al4·3SiO4·5H2O, etc.), magnesium silicate (M g2SiO4, MgSiO3, etc.), calcium silicate (Ca2SiO4, etc.), calcium aluminum silicate (Al2O3·CaO·2SiO2, etc.), calcium magnesium silicate (CaMgSiO4), calcium carbonate (CaCO3), zirconium oxide (ZrO2), zirconium hydroxide [ZrO(OH)2·nH2O], zirconium carbonate [Zr(CO3)2], various zeolites, crystalline aluminosilicates containing charge-corrected hydrogen, alkali metals or alkaline earth metals, etc.

[0148] In the polymer composition of the present invention, the amount of the filler comprising [B] silica and [C] carbon black is preferably 30 parts by mass or more, and more preferably 40 parts by mass or more, relative to 100 parts by mass of the rubber component. In addition, the amount of the filler comprising [B] silica and [C] carbon black is preferably 350 parts by mass or less, and more preferably 200 parts by mass or less. If the amount of the filler in the polymer composition is within the range, when the polymer composition of the present invention is used for the tread manufacturing purpose of the tire, the low rolling resistance of the tire, the braking performance on the wet road surface, the handling performance on the dry road surface, and the wear resistance can be taken into account to a higher degree.

[0149] [D] Other rubber components

[0150] The polymer composition of the present disclosure may further contain a rubber component other than the modified copolymer (P) (also referred to as "[D] other rubber component"). As the [D] other rubber component, at least one diene rubber selected from the group consisting of natural rubber, isoprene rubber, butadiene rubber, emulsion polymerized styrene-butadiene rubber, solution polymerized styrene-butadiene rubber, hydrogenated styrene-butadiene rubber, butyl rubber, halogenated butyl rubber and ethylene-propylene rubber, and a rubber component different from the modified copolymer (P) can be preferably used. [D] Other rubber component preferably further contains at least one rubber component selected from the group consisting of natural rubber, butadiene rubber, emulsion polymerized styrene-butadiene rubber, solution polymerized styrene-butadiene rubber and hydrogenated styrene-butadiene rubber, and a rubber component different from the modified copolymer (P). When the [D] other rubber component is mixed with the modified copolymer (P), it can be mixed during kneading in a conventional internal mixer, roll or the like, or it can be pre-mixed in a solution state after polymerization and then dried for use.

[0151] Regarding the ratio of the modified copolymer (P) to [D] other rubber components, the modified copolymer (P) is preferably 10 to 95 parts by mass and the [D] other rubber components are preferably 5 to 90 parts by mass, with respect to 100 parts by mass of the rubber component (the total amount of the modified copolymer (P) and [D] other rubber components). It is more preferred that the modified copolymer (P) is 20 to 90 parts by mass and the [D] other rubber components are 10 to 80 parts by mass.

[0152] In the present disclosure, from the viewpoint of further improving dry grip performance, wet grip performance and burst resistance, liquid rubber may also be used as part or all of [D] other rubber components. Examples of liquid rubber include liquid polyisoprene (liquid IR), liquid polybutadiene (liquid BR), liquid styrene-butadiene copolymer (liquid SBR) and liquid ethylene-propylene copolymer (liquid EP). For example, liquid SBR having a weight average molecular weight of 1,000 to 100,000, preferably 2,000 to 80,000, may be used. In addition, the weight average molecular weight of the liquid rubber refers to the weight average molecular weight converted to polystyrene analyzed by gel permeation chromatography (GPC). Liquid rubber refers to a rubber having fluidity at 23°C.

[0153] [E] Silane coupling agent

[0154] In the present disclosure, a silane coupling agent [E] may be formulated to further improve the reinforcing property of silica. The silane coupling agent [E] is not particularly limited, and is preferably a sulfur-containing silane coupling agent. Examples of sulfur-containing silane coupling agents include bis(3-triethoxysilylpropyl)tetrasulfide, bis(3-triethoxysilylpropyl)disulfide, 3-trimethoxysilylpropylbenzothiazoletetrasulfide, γ-mercaptopropyltriethoxysilane, 3-octanoylthiopropyltriethoxysilane, and 3-[ethoxybis(3,6,9,12,15-pentaoxacosan-1-yloxy)silyl]-1-propanethiol.

[0155] The amount of the [E] silane coupling agent is preferably 1 to 20 parts by mass relative to 100 parts by mass of silica. If the amount of the [E] silane coupling agent is less than 1 part by mass, the amount is too small and the effect of improving the dispersibility of silica cannot be fully obtained. On the other hand, if the amount of the [E] silane coupling agent exceeds 20 parts by mass, the processability and elongation at break may decrease. The amount of the [E] silane coupling agent is more preferably 5 to 15 parts by mass relative to 100 parts by mass of silica. As a coupling agent, only one type may be used, or two or more types may be used in combination.

[0156] [F] Cross-linking agent

[0157] The polymer composition of the present disclosure may contain a cross-linking agent [F]. By containing a cross-linking agent [F] in the polymer composition of the present disclosure, a cross-linked product with further improved strength and wear resistance can be obtained. Examples of the cross-linking agent include sulfur, sulfur halides, organic peroxides, quinone dioximes, organic polyamine compounds, and alkylphenol resins having a hydroxymethyl group, and sulfur is generally used. The amount of the cross-linking agent [F] is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 3 parts by mass, relative to 100 parts by mass of the total amount of the rubber component contained in the polymer composition.

[0158] In the polymer composition, in order to extend the elastomer with oil, a commonly used processing oil can also be formulated. The processing oil is formulated in the polymer composition, for example, by directly adding the oil to the rubber formulation. As preferred processing oils, various oils known in the art can be listed, for example, aromatic oils, paraffin oils, naphthenic oils, vegetable oils, sunflower oils, soybean oils, and oils with low content of polycyclic aromatic compounds (low polycyclic aromatic hydrocarbons (PCA) oils), such as mild extraction solvents (MES: mild extraction solvate), oils obtained by treating aromatic extracts from distilled oils (TDAE: treated distillate aromatic extract), special aromatic extracts from residual oils (SRAE: special residual aromatic extract) and heavy naphthenic oils, etc. Examples of commercially available MES, TDAE, and SRAE include Catenex SNR (heavy paraffin obtained by dewaxing distilled oil with a solvent) manufactured by Shell as MES, Vivatec 500 manufactured by H&R Wasag AG as TDAE, and NC140 manufactured by Japan Energy Corp. as SRAE. The blending amount of the processing oil is preferably 10 to 100 parts by mass based on 100 parts by mass of the total amount of the rubber component contained in the polymer composition.

[0159] In addition to the above components, the polymer composition may also contain various additives commonly used in polymer compositions for manufacturing tire rubber, such as antioxidants, zinc flower, stearic acid, softeners, vulcanization accelerators, extenders, resins, vulcanization aids, processing aids, and scorch retardants. The proportion of these additives may be appropriately selected according to the various components within the range that does not impair the effects of the present disclosure.

[0160] The polymer composition of the present disclosure is kneaded with components formulated as needed in addition to the polymer components using a kneading machine such as an open kneading machine (e.g., a roll) or a closed kneading machine (e.g., an internal mixer), and crosslinked (vulcanized) after molding, thereby being applicable to various rubber products as a crosslinked product. Specifically, the cross-linked product of the present disclosure can be applied to tire applications such as tire tread, undertread, carcass, sidewall, bead part, etc.; sealing materials such as gaskets, gaskets, weather strips, and O-rings; inner and outer packaging surface materials for various vehicles such as automobiles, ships, airplanes, and railways; building materials; vibration-proof rubbers for industrial machinery or equipment; various hoses and hose covers such as diaphragms, rollers, radiator hoses, and air hoses; belts such as power transmission belts; linings; dust boots; medical equipment materials; fenders; insulating materials for wires; and other industrial products.

[0161] According to the method for producing the modified conjugated diene polymer disclosed in the present invention, a modified conjugated diene polymer having crosslinked products with good physical properties required for tire applications such as wet grip performance, wear resistance and strength can be obtained. Therefore, the polymer composition containing the modified conjugated diene polymer obtained in the present invention can be particularly preferably used as a material for the tread, sidewall, or both of the tires.

[0162] The tire can be manufactured according to conventional methods. For example, a polymer composition is mixed using a mixer, and the polymer composition formed into a sheet is arranged at a predetermined position (for example, the outer side of the frame in the case of a sidewall) according to conventional methods and vulcanized to form a tread rubber or a sidewall rubber, thereby obtaining a pneumatic tire.

[0163] Through the present disclosure described in detail above, the following aspects are provided.

[0164] [1] A modified conjugated diene polymer comprising: a structural unit derived from a conjugated diene compound; and a structural unit derived from an aromatic vinyl compound, wherein the glass transition temperature measured according to JIS K 6240:2011 is defined as Tg r (unit: K), the glass transition temperature obtained by the above formula (1) is defined as Tg cl (Unit: K), Tg r With Tg cl The relationship of the above formula (2) is satisfied.

[0165] [2] The modified conjugated diene polymer according to [1], wherein the 1 The value θst (unit: mass %) calculated by the H-NMR spectrum using the above-mentioned formula (3) was 15 to 60.

[0166] [3] The conjugated diene polymer according to [1] or [2], wherein the content of the structural unit derived from the aromatic vinyl compound is 3% by mass to 55% by mass based on the total amount of the structural units constituting the polymer.

[0167] [4] The modified conjugated diene polymer according to any one of [1] to [3], wherein the vinyl bond content in the structural unit derived from the conjugated diene compound is 25% by mass or more.

[0168] [5] The modified conjugated diene polymer according to any one of [1] to [4], comprising a partial structure derived from a compound having one or more elements selected from the group consisting of nitrogen, silicon, sulfur, oxygen and phosphorus.

[0169] [6] The modified conjugated diene polymer according to any one of [1] to [5], wherein the glass transition temperature measured according to JIS K6240:2011 is -20°C or lower.

[0170] [7] A polymer composition comprising the modified conjugated diene polymer according to any one of [1] to [6] above; and at least one filler selected from the group consisting of silica and carbon black.

[0171] [8] The polymer composition according to [7] further contains at least one rubber component selected from the group consisting of natural rubber, isoprene rubber, butadiene rubber, emulsion polymerized styrene-butadiene rubber, solution polymerized styrene-butadiene rubber, hydrogenated styrene-butadiene rubber, butyl rubber, halogenated butyl rubber and ethylene-propylene rubber, and different from the modified conjugated diene polymer.

[0172] [9] A cross-linked product obtained by cross-linking the polymer composition according to [7] or [8].

[0173]

[10] A tire having a tread, a sidewall, or both formed using the polymer composition according to [7] or [8].

[0174]

[11] A method for producing a modified conjugated diene polymer according to any one of [1] to [6], comprising a polymerization step of polymerizing monomers comprising a conjugated diene compound and an aromatic vinyl compound in the presence of at least one polymerization initiator selected from the group consisting of alkali metal compounds and alkaline earth metal compounds, and a potassium compound (excluding the polymerization initiator), wherein in the polymerization step, polymerization is started by using a portion of the total amount of the conjugated diene compound used in the polymerization as an initial charge, and the remaining conjugated diene compound is added for a predetermined time in the middle of the polymerization to continue the polymerization.

[0175]

[12] A method for producing a modified conjugated diene polymer according to

[11] , wherein the polymerization step is a step for obtaining a polymer having an active end, and the method further comprises a modification step of reacting the polymer having an active end with a compound having one or more elements selected from the group consisting of nitrogen, silicon, sulfur, oxygen and phosphorus.

[0176] Example

[0177] The following is a specific description based on examples, but the present invention is not limited to these examples. In addition, "parts" and "%" in the examples and comparative examples are based on mass unless otherwise specified. The measurement methods of various physical property values ​​of polymers and crosslinked products are shown below.

[0178] [Evaluation of polymer and cross-linked products]

[0179] · Vinyl bond content (mass %): measured by 400 MHz 1 Determined by H-NMR.

[0180] Bonded styrene content (mass %): measured by 400 MHz 1 Determined by H-NMR.

[0181] ·Use specific chain content ratio (mass % relative to the total amount of styrene): 400MHz 1 The results of H-NMR measurement were calculated as follows. 1 In the H-NMR spectrum, the ratio of the integral value Σ(a) of the chemical shift range of (a) to the sum Σ(a, b) of the integral values ​​of the chemical shift ranges of (a) and (b) below is calculated as a percentage, and its value is set to 2.5 times, which is set as the content ratio θst [mass %] of the specific chain (refer to the following formula (3)).

[0182] (a)6.00≦σ<6.89

[0183] (b)6.89≦σ≦8.00

[0184] θst=[(Σ(a) / Σ(a,b))×2.5]×100…(3)

[0185] Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn): The molecular weight was determined based on a graph (GPC curve) of molecular weights in terms of polystyrene obtained by gel permeation chromatography (GPC). Specific measurement conditions of GPC are as follows.

[0186] (GPC measurement conditions)

[0187] Measuring instrument: HLC-8020 (manufactured by Tosoh Corporation)

[0188] Column: Two GMHhr-H (Tosoh) pipes connected in series

[0189] Detector: Differential refractometer RI-8020 (manufactured by Tosoh Corporation)

[0190] Eluent: Tetrahydrofuran

[0191] Column temperature: 40℃

[0192] Flow rate: 1.0mL / min

[0193] Sample concentration: 10mg / 20ml

[0194] · 1st peak weight average molecular weight: In the GPC curve obtained when measuring Mw, the weight average molecular weight in terms of polystyrene is determined for the peak with the smallest molecular weight, and this is defined as the 1st peak weight average molecular weight.

[0195] ·Monna viscosity (ML 1+4 , 100°C): Calculated in accordance with JIS K6300-1:2013, using an L rotor, under the conditions of 1 minute preheating, 4 minutes rotor operation time, and a temperature of 100°C.

[0196] Actual glass transition temperature Tg r : According to JIS K 6240:2011, the glass transition temperature is obtained from the inflection point of the DSC curve in the range of -100°C to 40°C. The specific measurement conditions of the glass transition temperature are as follows. In addition, since the measurement result is obtained as a Celsius temperature (°C), the measurement value obtained by DSC analysis (value to the last digit, unit: °C) is added with 273.15, converted into Kelvin (K), and the actual glass transition temperature Tg is obtained. r .

[0197] (DSC measurement conditions)

[0198] Measurement device: Q1000 Differential Scanning Calorimeter (DSC) (manufactured by TA Instruments)

[0199] Heating rate: 10℃ / min

[0200] <Synthesis of modified conjugated diene polymer>

[0201] <Example 1>:

[0202] In a nitrogen-purged autoclave reactor with a volume of 5 liters, 2250 g of cyclohexane, 2.5 mL of tetrahydrofuran as a vinyl content adjuster (randomizer), 0.06 mmol of potassium 4-dodecylbenzenesulfonate as a potassium compound, and 175 g of styrene and 150 g of 1,3-butadiene as polymerization monomers were loaded. After adjusting the temperature of the contents of the reactor to 35°C, 3.0 mmol of n-butyl lithium as a polymerization initiator was added to start polymerization. After confirming that the polymerization conversion rate reached 20% (equivalent to the moment when the temperature of the contents reached 45°C), 175 g of 1,3-butadiene (additional component) was added to the reactor at a constant supply rate over 23 minutes. The polymerization was carried out under adiabatic conditions, and the maximum temperature reached 85°C.

[0203] After confirming that the polymerization conversion rate reached 99% (after 35 minutes from the start of polymerization), 2.7 mmol of 3-(N,N-bistrimethylsilyl)aminopropylmethyldiethoxysilane was added as a terminal modifier, and stirred for 10 minutes. After adding 4.40 g of 2,6-di-tert-butyl-p-cresol as an antioxidant to the stirred polymer solution, the solvent was removed by steam stripping, and the modified conjugated diene polymer A-1 (hereinafter also referred to as "A-1") was obtained by drying using a hot roll adjusted to 130°C.

[0204] <Example 2> to <Example 12>:

[0205] Except that the types and amounts of the compounds used in the polymerization are shown in Table 1, modified conjugated diene polymers A-2 to A-12 (hereinafter, each polymer is also referred to as "A-2" to "A-12") were obtained by the same method as in Example 1. In addition, in Example 3, 2.7 mmol of piperidine was added as an initiator terminal modifier together with the solvent, the polymerization monomer, etc. In Example 11, 2.7 mmol of N-(trimethylsilyl)piperazine was added as an initiator terminal modifier together with the solvent, the polymerization monomer, etc.

[0206] <Example 13>:

[0207] In a nitrogen-purged autoclave reactor with a volume of 5 liters, 2500 g of cyclohexane, 2.8 mL of tetrahydrofuran as a vinyl content adjuster, 0.06 mmol of potassium 4-dodecylbenzenesulfonate as a potassium compound, and 88 g of styrene and 75 g of 1,3-butadiene as polymerization monomers were loaded. After adjusting the temperature of the contents of the reactor to 35°C, 3.3 mmol of n-butyl lithium was added as a polymerization initiator to start polymerization. After confirming that the polymerization conversion rate reached 20% (equivalent to the moment when the temperature of the contents reached 50°C), 338 g of 1,3-butadiene (additional component) was added to the reactor at a constant supply rate over 35 minutes. The polymerization was carried out under adiabatic conditions, and the maximum temperature reached 85°C.

[0208] After confirming that the polymerization conversion rate reached 99% (45 minutes after the start of polymerization), 2.7 mmol of 3-(N,N-bistrimethylsilyl)aminopropylmethyldiethoxysilane was added as a terminal modifier, and the mixture was stirred for 10 minutes. After adding 4.80 g of 2,6-di-tert-butyl-p-cresol as an anti-aging agent to the stirred polymer solution, the solvent was removed by steam stripping, and the mixture was dried using a hot roll at a temperature of 130° C. to obtain a modified conjugated diene polymer A-13 (hereinafter also referred to as “A-13”).

[0209] <Example 14> to <Example 17>:

[0210] Except that the types and amounts of the compounds used in the polymerization were as shown in Table 1 or Table 2, modified conjugated diene polymers A-14 to A-17 (hereinafter, each polymer is also referred to as "A-14" to "A-17") were obtained by the same method as in Example 13.

[0211] <Example 18>:

[0212] In a nitrogen-purged autoclave reactor with a volume of 5 liters, 2000 g of cyclohexane, 11.2 mL of tetrahydrofuran as a vinyl content adjuster, 0.05 mmol of potassium 4-dodecylbenzenesulfonate as a potassium compound, and 100 g of styrene and 150 g of 1,3-butadiene as polymerization monomers were loaded. After adjusting the temperature of the contents of the reactor to 35°C, 2.7 mmol of n-butyl lithium as a polymerization initiator was added to start polymerization. After confirming that the polymerization conversion rate reached 20% (equivalent to the moment when the temperature of the contents reached 50°C), 250 g of 1,3-butadiene (additional component) was added to the reactor at a constant supply rate over 25 minutes. The polymerization was carried out under heat insulation conditions, and the maximum temperature reached 85°C.

[0213] After confirming that the polymerization conversion rate reached 99% (35 minutes after the start of polymerization), 2.4 mmol of 3-(N,N-bistrimethylsilyl)aminopropylmethyldiethoxysilane was added as a terminal modifier, and the mixture was stirred for 10 minutes. After adding 4.00 g of 2,6-di-tert-butyl-p-cresol as an anti-aging agent to the stirred polymer solution, the solvent was removed by steam stripping, and the mixture was dried using a hot roll at a temperature of 130° C. to obtain a modified conjugated diene polymer A-18 (hereinafter also referred to as “A-18”).

[0214] <Comparative Example 1>:

[0215] Except adding 0.5 mL of methanol instead of 2.7 mmol of 3-(N,N-bistrimethylsilyl)aminopropylmethyldiethoxysilane, conjugated diene polymer A-19 (hereinafter, also referred to as "A-19") was obtained by the same method as Example 1. A-19 is an unmodified conjugated diene polymer. In addition, the modified conjugated diene polymer and the unmodified conjugated diene polymer are also marked as "(modified) conjugated diene polymer".

[0216] <Comparative Example 2>:

[0217] A modified conjugated diene polymer A-20 (hereinafter also referred to as "A-20") was obtained by the same method as in Example 1 except that the types and amounts of the compounds used in the polymerization were as shown in Table 2. In the polymerization of Comparative Example 2, no potassium compound was added to the reactor.

[0218] <Comparative Example 3>:

[0219] The types and amounts of the compounds used in the polymerization were as shown in Table 2. 175 g of 1,3-butadiene (additional component) was added to the reactor over 15 minutes to be added during the polymerization. A modified conjugated diene polymer A-21 (hereinafter also referred to as "A-21") was obtained by the same method as in Example 1.

[0220] <Comparative Example 4>:

[0221] The types and amounts of the compounds used in the polymerization are shown in Table 2, and 175 g of 1,3-butadiene (additional component) added in the middle of the polymerization is added to the reactor over 15 minutes. A modified conjugated diene polymer A-22 (hereinafter, also referred to as "A-22") is obtained by the same method as in Example 1. In addition, in the polymerization of Comparative Example 4, no potassium compound is added to the reactor.

[0222] <Comparative Example 5>:

[0223] The types and amounts of the compounds used in the polymerization were as shown in Table 2. 128 g of 1,3-butadiene (additional component) was added to the reactor over 10 minutes to be added during the polymerization. A modified conjugated diene polymer A-23 (hereinafter also referred to as "A-23") was obtained by the same method as in Example 13.

[0224] <Comparative Example 6>:

[0225] The types and amounts of the compounds used in the polymerization are shown in Table 2, and 250 g of 1,3-butadiene (additional component) added during the polymerization was added to the reactor over 20 minutes. A modified conjugated diene polymer A-24 (hereinafter also referred to as "A-24") was obtained by the same method as in Example 13. In addition, in the polymerization of Comparative Example 6, no potassium compound was added to the reactor.

[0226]

[0227]

[0228] In Tables 1 and 2, the abbreviations of the compounds are as follows.

[0229] ·DBS-K: Potassium 4-dodecylbenzenesulfonate

[0230] IM-1: N-trimethylsilylpiperazine

[0231] ·M-1: 3-(N,N-bistrimethylsilyl)aminopropylmethyldiethoxysilane

[0232] M-2: N-(3-dimethoxy(methyl)silyl)propyl-1-(4-(((3-(diethoxy)(methyl)silyl)propyl)imino)phenyl)methanimine

[0233] ·M-3: 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azosilyl

[0234] M-4: N-(3-(1H-imidazol-1-yl)propyl)-3-(trimethoxysilyl)-N-(3-(trimethoxysilyl)propyl)propane-1-amine

[0235] ·M-5: 3-(Trimethylsilylmercapto)propyltrimethoxysilane

[0236] ·M-6: 3-(Diphenylphosphino)propylmethyldiethoxysilane

[0237] M-7: 1-phenyl-N-(3-(triethoxysilyl)propyl)methanimine

[0238] [Chemistry 8]

[0239]

[0240] The analysis results of the synthesized (modified) conjugated diene polymers (A-1 to A-24) are shown in Tables 3 and 4. In addition, the estimated glass transition temperature Tg of each polymer is cl (Unit: K) is obtained by using the above formula (1) to the second decimal place (round off the third decimal place). r -Tg cl ) can be obtained by: r Subtract the estimated glass transition temperature Tg cl The value after the decimal point is rounded off to the nearest whole number. In Tables 3 and 4, the "number of endothermic peaks" indicates the number of peaks in a differential curve obtained by DSC measurement of the (modified) conjugated diene polymer.

[0241] [Table 3]

[0242]

[0243] <Production of polymer composition and cross-linked product>

[0244] [Examples 1 to 12 and Comparative Examples 1 to 4]

[0245] The (modified) conjugated diene polymers A-1 to A-12 and A-19 to A-22 prepared as described above are respectively used to prepare the components by the formulation shown in the following Table 5, and the components are kneaded to prepare the polymer composition. In addition, the units of the numerical values ​​in Table 5 are parts by mass. The kneading is carried out in the following manner. A plasto mill (content: 250 mL) with a temperature control device is used. First, as the first stage of kneading, the (modified) conjugated diene polymer, butadiene rubber, silica, silane coupling agent, carbon black, extender oil, stearic acid, anti-aging agent and zinc oxide are mixed and kneaded under the conditions of a filling rate of 72% and a rotation speed of 60 rpm. Then, as the second stage of kneading, the obtained formulation is cooled to room temperature, and sulfur and a vulcanization accelerator are mixed and kneaded. The obtained polymer composition is molded, and a cross-linked product (vulcanized rubber) is obtained by vulcanization and press vulcanization at 160°C for a specified time. In addition, wet grip performance, abrasion resistance, and strength were evaluated as follows. The results are shown in Table 6.

[0246] (1) Wet grip performance (tan δ at 0°C): Using vulcanized rubber as a test sample, ARES-RDA (manufactured by TA Instruments) was used to measure the loss coefficient (tan δ (0°C)) under the conditions of a shear strain of 0.14%, an angular velocity of 100 radians per second, and 0°C. The measurement results are expressed as an index with Comparative Example 2 being 100. A larger value indicates better wet grip performance.

[0247] (2) Abrasion resistance (DIN abrasion test): The vulcanized rubber was used as a test sample and the test was performed at 25°C with a load of 10 N using a DIN abrasion tester (manufactured by Toyo Seiki Co., Ltd.) in accordance with JIS K6264. The test results were expressed as an index with Comparative Example 2 being 100. A larger value indicates better abrasion resistance.

[0248] (3) Strength (tensile test): A tensile test was performed using vulcanized rubber as a test specimen in accordance with JIS K6251:2010. A dumbbell No. 3 was used as a test specimen, and the stress at break (TB, unit: MPa) and the elongation at break (EB, unit: %) were measured at room temperature. The larger the values ​​of TB and EB, the greater the breaking strength, and the higher the mechanical strength of the material, and the better. The strength is represented by the tensile product (= (TB×EB)), which is represented by an index with Comparative Example 2 being 100. It can be said that the larger the value, the higher the strength, and the better.

[0249] [Table 5]

[0250] Prescription Number of copies (Modified) conjugated diene polymer 70 Butadiene rubber*1 30 Silicon dioxide*2 75 Silane coupling agent*3 6 Carbon black*4 5 Filling oil*5 30 Stearic acid 2 Anti-aging agent*6 1 Zinc Oxide 3 Vulcanization accelerator CZ-G*7 1.8 Vulcanization accelerator D*8 1.5 sulfur 1.5

[0251] *1) BR01 manufactured by ENEOS Materials Co., Ltd.

[0252] *2) ZEOSIL 1165MP manufactured by Solvay

[0253] *3) Si75 manufactured by Evonik

[0254] *4) Made by Mitsubishi Chemical Corporation, DIABLACK N330

[0255] *5) Processing oil T-DAE manufactured by ENEOS

[0256] *6) Ozonone 6C manufactured by Seiko Chemical

[0257] *7) Nocceler CZ-G manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0258] *8) Nocceler D manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0259]

[0260] [Examples 13 to 17 and Comparative Example 5]

[0261] The modified conjugated diene polymers A-13 to A-17 and A-23 were prepared by mixing the components according to the mixing formula shown in Table 5, and kneading was performed in the same manner as in Examples 1 to 12 and Comparative Examples 1 to 4 to prepare polymer compositions. The Monet viscosity (ML) of the obtained polymer compositions was measured by the following method: 1+4 , 100°C), and the index is expressed by 100 for Comparative Example 5. In addition, a crosslinked product (vulcanized rubber) was prepared using the obtained polymer composition, and the wet grip performance, abrasion resistance and strength were evaluated by the same method as in Examples 1 to 12 and Comparative Examples 1 to 4. The measurement results are expressed by an index by 100 for Comparative Example 5. The results are shown in Table 7.

[0262] (4) Mena viscosity (ML) 1+4 , 100°C): The polymer composition was used as a sample for measurement, and the L rotor was used according to JIS K6300-1:2013, under the conditions of preheating for 1 minute, rotor operation time for 4 minutes, and temperature of 100°C. The measurement results are expressed as an index with Comparative Example 5 being 100. The smaller the value, the better the processability.

[0263] [Table 7]

[0264]

[0265] [Example 18 to Example 23 and Comparative Example 6 to Comparative Example 8]

[0266] The modified conjugated diene polymers A-15 and A-21 prepared as described above were used to prepare the components according to the formulation shown in Table 8 below, and kneaded in the same manner as in Examples 1 to 12 and Comparative Examples 1 to 4 to prepare a polymer composition. A crosslinked product (vulcanized rubber) was prepared using the obtained polymer composition, and the wet grip performance, abrasion resistance and strength were evaluated in the same manner as in Examples 1 to 12 and Comparative Examples 1 to 4. The measurement results are shown in Table 8 with the index of Comparative Example 6 being 100 for Example 18, the index of Comparative Example 7 being 100 for Example 19, and the index of Comparative Example 8 being 100 for Examples 20 to 23. The results are shown in Table 8.

[0267] [Table 8]

[0268]

[0269] From the results in Table 6, it can be seen that the vulcanized rubbers produced from the polymer compositions of Examples 1 to 12 have significantly improved wet grip performance, wear resistance and strength compared to the vulcanized rubbers produced from the polymer compositions of Comparative Examples 1 to 4.

[0270] In addition, as can be seen from the results of Table 7, the vulcanized rubbers produced from the polymer compositions of Examples 13 to 17 showed significantly improved wet grip performance, wear resistance, and strength compared to the vulcanized rubber produced from the polymer composition of Comparative Example 5. In particular, the polymer compositions of Examples 13 to 16 also showed improved processability.

[0271] Furthermore, from the results in Table 8, it can be seen that the vulcanized rubbers produced from the polymer compositions of Examples 18, 19, and 20 have significantly improved wet grip performance, wear resistance, and strength compared to the vulcanized rubbers produced from the polymer compositions of Comparative Examples 6, 7, and 8, respectively. In addition, in Examples 21 to 23 to which a resin is further added, not only the vulcanized rubbers produced from the polymer composition of Comparative Example 8 but also the vulcanized rubbers produced from the polymer composition of Example 20 have significantly improved wet grip performance, wear resistance, and strength compared to the vulcanized rubbers.

[0272] These results confirm that a modified conjugated diene polymer whose measured and estimated glass transition temperatures satisfy the relationship of formula (2) can provide a cross-linked product having excellent wet grip performance and abrasion resistance, high strength, and excellent various properties as a rubber.

Claims

1. A modified conjugated diene polymer comprising: Structural units derived from conjugated diene compounds; as well as Structural units derived from aromatic vinyl compounds, When the glass transition temperature measured according to Japanese Industrial Standard K 6240: 2011 is defined as Tg r (unit: K), the glass transition temperature obtained by the following formula (1) is defined as Tg cl (Unit: K), Tg r With Tg cl The relationship of the following formula (2) is satisfied. [Number 1] Tg r -Tg cl ≦-6.0…(2) (In equation (1), W Ar is the mass fraction of the structural unit derived from the aromatic vinyl compound in the modified conjugated diene polymer, satisfying 0≦W Ar ≦1. ) 2. The modified conjugated diene polymer according to claim 1, wherein According to the determination using deuterated chloroform as solvent 1 The value θst (unit: mass %) calculated by the following equation (3) from the H-nuclear magnetic resonance spectrum was 15 to 60. θst=[(Σ(a) / Σ(a,b))×2.5]×100 …(3) (In formula (3), Σ(a) represents the integral value of the chemical shift range of 6.00≦σ<6.89; Σ(a,b) represents the total of the integral values ​​of the chemical shift ranges of 6.00≦σ<6.89 and 6.89≦σ≦8.00.) ) 3. The modified conjugated diene polymer according to claim 1, wherein The content ratio of the structural unit derived from the aromatic vinyl compound is 3% by mass to 55% by mass based on the total amount of the structural units constituting the polymer.

4. The modified conjugated diene polymer according to claim 1, wherein The vinyl bond content in the structural unit derived from the conjugated diene compound is 25% by mass or more. 5 . The modified conjugated diene polymer according to claim 1 , comprising a partial structure derived from a compound having one or more elements selected from the group consisting of nitrogen, silicon, sulfur, oxygen and phosphorus.

6. The modified conjugated diene polymer according to claim 1, wherein The glass transition temperature measured according to Japanese Industrial Standard K 6240:2011 is -20°C or lower.

7. A polymer composition comprising: The modified conjugated diene polymer according to any one of claims 1 to 6; and At least one filler selected from the group consisting of silica and carbon black.

8. The polymer composition according to claim 7 further contains at least one rubber component selected from the group consisting of natural rubber, isoprene rubber, butadiene rubber, emulsion polymerized styrene-butadiene rubber, solution polymerized styrene-butadiene rubber, hydrogenated styrene-butadiene rubber, butyl rubber, halogenated butyl rubber and ethylene-propylene rubber, and different from the modified conjugated diene polymer.

9. A cross-linked product, formed by cross-linking the polymer composition according to claim 7.

10. A tire having a tread, a sidewall, or both formed using the polymer composition according to claim 7.

11. A method for producing a modified conjugated diene polymer, the method for producing a modified conjugated diene polymer according to any one of claims 1 to 6, comprising: A polymerization step of polymerizing monomers containing a conjugated diene compound and an aromatic vinyl compound in the presence of at least one polymerization initiator selected from the group consisting of alkali metal compounds and alkaline earth metal compounds and a potassium compound (except the polymerization initiator), In the polymerization step, a portion of the total amount of the conjugated diene compound used in the polymerization is used as an initial charge to start polymerization, and the remaining conjugated diene compound is added over a predetermined time during the polymerization to continue polymerization.

12. The method for producing a modified conjugated diene polymer according to claim 11, wherein: The polymerization step is a step of obtaining a polymer having an active terminal. The method further includes a modification step of reacting the polymer having an active terminal with a compound having one or more elements selected from the group consisting of nitrogen, silicon, sulfur, oxygen, and phosphorus.

Citation Information

Patent Citations

  • Preparation of polymer, polymer obtained and rubber composition using the polymer

    JP1999349632A

  • Modified conjugated dienic polymer composition

    JP2002284930A

  • Polybutadiene rubber, rubber composition for tire, and tire

    JP2009084413A

  • Modified conjugated diene polymer, production method therefor, and polymer composition

    JP2009227858A

  • Rubber composition for tire and pneumatic tire

    JP2011140613A